2011
DOI: 10.1007/s10865-011-9345-5
|View full text |Cite
|
Sign up to set email alerts
|

The association between chronic stress type and C-reactive protein in the multi-ethnic study of atherosclerosis: does gender make a difference?

Abstract: Objective To examine how chronic stress in major life domains [relationship, work, sympathetic-caregiving, financial] relates to CVD risk, operationalized using the inflammatory marker C-Reactive Protein (CRP), and whether gender differences exist. Methods Participants were 6583 individuals aged 45 to 84 years, recruited as part of the Multi-Ethnic Study of Atherosclerosis (MESA). Demographic and behavioral factors, health history, and chronic stress were self-reported. CRP was obtained through venous blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 85 publications
2
56
0
Order By: Relevance
“…For men, however, the loss of normal regulatory feedback reflected an imbalance characterized by an enhanced release of CORT coupled with attenuated inflammation, a pattern that was associated with increasing trait anxiety, diminishing quality of sleep, and increasing frequency of daytime dysfunction. Although previous studies have reported gender differences in the relation of the individual components of the CORT/CRP ratio to MDD, severity of depressive symptoms, and vulnerability factors (e.g., Maes et al, 1988; Shivpuri et al, 2011; Zobel et al, 2004), to our knowledge these are the first data to suggest gender specificity in the relation of vulnerability factors to distinct and gender-specific uncoupling of neuro-immune feedback mechanisms.…”
Section: Discussionmentioning
confidence: 49%
“…For men, however, the loss of normal regulatory feedback reflected an imbalance characterized by an enhanced release of CORT coupled with attenuated inflammation, a pattern that was associated with increasing trait anxiety, diminishing quality of sleep, and increasing frequency of daytime dysfunction. Although previous studies have reported gender differences in the relation of the individual components of the CORT/CRP ratio to MDD, severity of depressive symptoms, and vulnerability factors (e.g., Maes et al, 1988; Shivpuri et al, 2011; Zobel et al, 2004), to our knowledge these are the first data to suggest gender specificity in the relation of vulnerability factors to distinct and gender-specific uncoupling of neuro-immune feedback mechanisms.…”
Section: Discussionmentioning
confidence: 49%
“…Chronic stress burden (8 items) 20,21 asked participants about ongoing stressors in important life domains (health, work, relationships) that have lasted for at least 6 months. A score was created by summing the number of ongoing stressors reported (range 0–8), which was later categorized into number of reported stressors (0, 1, 2, ≥3).…”
Section: Methodsmentioning
confidence: 99%
“…This measure has been used in prior multi-ethnic cohort studies (29, 30). The 10-item Perceived Stress Scale (PSS10) was used to assess appraisals of recent stress (e.g., In the past month, how often have you found that you could not cope with all the things that you had to do?…”
Section: Methodsmentioning
confidence: 99%